2008
DOI: 10.1016/j.jasms.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption/ionization mass spectrometry on porous silica and alumina for peptide mass fingerprinting

Abstract: We investigated a variant of desorption/ionization on porous silicon (DIOS) mass spectrometry utilizing an aqueous suspension of either porous silica gel or porous alumina (pore size of 60 and 90 Å, respectively). Laser desorption/ionization (LDI) from samples directly deposited on a stainless steel surface without any inorganic substrates was also achieved. Synthetic peptides designed to cover large sequence diversity constituted our model compounds. Sample preparation, including material conditioning, peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…It is worth noting that the selection of DESI solvent could be considered as similar to the selection of MALDI matrix as manipulation of the chemistry accompanying ambient ionization can be used to optimize chemical analysis and a recent review of the subject has been published [12]. A comprehensive review of matrixfree methods [104] describes methods such as desorptionionization on silicon (DIOS) which is as a matrix-free method for small molecule analysis [75,105], and has also been show to improve peptide coverage in PMF MALDI applications [106]. This has also been proven suitable for MSI, through the transfer of target analytes to the DIOS surface through contact with the tissue of interest [75].…”
Section: Choice Of Matrixmentioning
confidence: 99%
“…It is worth noting that the selection of DESI solvent could be considered as similar to the selection of MALDI matrix as manipulation of the chemistry accompanying ambient ionization can be used to optimize chemical analysis and a recent review of the subject has been published [12]. A comprehensive review of matrixfree methods [104] describes methods such as desorptionionization on silicon (DIOS) which is as a matrix-free method for small molecule analysis [75,105], and has also been show to improve peptide coverage in PMF MALDI applications [106]. This has also been proven suitable for MSI, through the transfer of target analytes to the DIOS surface through contact with the tissue of interest [75].…”
Section: Choice Of Matrixmentioning
confidence: 99%
“…In the search for an alternative method to conventional MALDI-MS peptide mass fingerprinting, various 'matrix-free' LDI analyses have been undertaken in the laboratory for peptide detection starting with commercially available inert materials, which were compared to the original method of Siuzdak on porous etched silicon (DIOS-chips). Porous chromatography materials (silica gel, reversed-phase silica gel and alumina, pore size of 60 and 90 Å), carbon powder (scratched pencil lead), silicon-based chips (NALDI™ target) [26,27] and more recently diamond nanowires have been investigated [28]. Among all inert studied substrates, silicon-based nanostructured materials provided the most sensitive peptide detection and were thus selected for further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Other inorganic materials are also used to assist LDI, such as graphite [33], carbon nanomaterials [34][35][36], nanodiamonds [37], porous alumina [38], nano-ZnO [39,40], EuF 3 hollow hexagonal nanodisks [41], silver nanoparticles [42], HgTe nanostructures [43], platinum nanoflowers [44], manganese oxide nanoparticles [45], Fe 3 O 4 particles [46], fullerene-derivatized silica [47] and germanium nanodots [48], among others. Recently, we have shown that quantum dots (QDs) of cadmium selenide and cadmium selenide covered with cadmium sulfide can also be used to assist LDI [49].…”
Section: Nanomaterial-assisted Laser Desorption Ionizationmentioning
confidence: 99%